ESTIMASI PEMBEBANAN TRANSFORMATOR GARDU INDUK 150 KV - Bawan, Elias K. (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2013)
Development of an area, such as Yogyakarta is directly proportional to consumption of power in that area. Transformer of 150 KV Wirobrajan substation, 60 MVA, is one of main equipment in power system. Load forecasting on this research using daily average peak load data during five years that is since 2003 to 2008. Based on the analysis of the result of exponential model approach method, the equation Y = 5.29 e 0.04057X is obtained. By using this model, it is found that average load growth forecasting of the transformer during 2009 to 2025, is suitable to supply 50.89 MVA of load demand (85% of full load). Moreover, model Y = 20.18 + 0.44X1 + 0.07X2 is found using polynomial method. In 2025, the transformer, based on polynomial method, can deliver power 80.07 MVA (about 80.07% of full load). Finally, load current was 230.72 A, in 2025. Keywords: Power demand, transformer capacity, exponential trend